The Gibberellin Producer Fusarium fujikuroi: Methods and Technologies in the Current Toolkit - Cen, Yu-Ke; Lin, Jian-Guang; Wang, You-Liang; Wang, Jun-You; Liu, Zhi-Qiang; Zheng, Yu-Guo (Frontiers in Bioengineering and Biotechnology, 2020)
In recent years, there has been a noticeable increase in research interests on the Fusarium species, which includes prevalent plant pathogens and human pathogens, common microbial food contaminants and industrial microbes. Taken the advantage of gibberellin synthesis, Fusarium fujikuroi succeed in being a prevalent plant pathogen. At the meanwhile, F. fujikuroi was utilized for industrial production of gibberellins, a group of extensively applied phytohormone. F. fujikuroi has been known for its outstanding performance in gibberellin production for almost 100 years. Research activities relate to this species has lasted for a very long period. The slow development in biological investigation of F. fujikuroi is largely due to the lack of efficient research technologies and molecular tools. During the past decade, technologies to analyze the molecular basis of host-pathogen interactions and metabolic regulations have been developed rapidly, especially on the aspects of genetic manipulation. At the meanwhile, the industrial fermentation technologies kept sustained development. In this article, we reviewed the currently available research tools/methods for F. fujikuroi research, focusing on the topics about genetic engineering and gibberellin production.